Presentation, Prescription Pattern and Time Taken To Discharge From An Emergency Department Of Eastern Nepal (Health Renaissance, 2016)
Background: It is a great challenge for a doctor to give proper care and discharge because of overcrowding in emergency units like ours. The clinical records in emergency are an essential document that reflects the quality of care which is given to the patient.Objectives: To find out the time taken for discharge from emergency and to find out the current trend of problems presenting to emergency and their prescription pattern.Methods: A retrospective descriptive hospital based study was carried out using all emergency discharged patients’ case sheet records from 14th April to 14th May 2013. A number of 1022 files were analyzed. Results: Out of 1022 discharge files, majority (72%) of the patients included Australian Triage Score (ATS) 3. Patients with ATS 5 had a mean duration of stay of 24 hours whereas ATS 2, 3, 4 patients had mean duration of stay of 10.10 hours, 8.75 hours and 5.48 hours respectively. Most common clinical presentation was trauma (31.3%). Out of 1022 patients, 504 (49%) were treated with antibiotics. Cefixime was the most frequently administered antibiotics (24.7%). Of all 506 patients received analgesic, mostly diclofenac (30.8%), 79 received antispasmodic drugs, mostly hyoscine butyl bromide (6.2%), and antipyretics mostly paracetamol. Proton pump inhibitors (PPI) were used in 594 (58.1%) patients mostly pantoprazole (47.2%). Conclusion: Sicker patients had longer duration of stay in the emergency unit. Trauma is the most common presentation, analysis, antibiotics and PPL are the most commonly prescribed which show in the emergency unit.Health Renaissance 2014;12(3): 209-214